Tourmaline from the Solnechnoe tin deposit, Khabarovsk Krai, Russia. (11th April 2020) - Baksheev, Ivan A.; Vigasina, Marina F.; Yapaskurt, Vasily O.; Bryzgalov, Igor A.; Gorelikova, Nina V.
Abstract: Tourmaline from the Solnechnoe hydrothermal granitoid-related tin deposit in the Khabarovsk Krai, Russian Far East has been studied with electron microprobe, infrared and Mössbauer spectroscopy. Tourmaline formed in three distinct stages with different types of chemical substitution. Tourmaline from the first unmineralised stage is classified as dravite or schorl, which could be enriched locally in Ca, the X -site vacancy and F. This tourmaline is characterised by the Fe ↔ Mg and X vacancy + Al ↔ Na + Fe substitutions. The second, molybdenum-stage tourmaline, is schorl–dravite and fluor-schorl–fluor-dravite enriched in Ca, and a few compositions belong to the calcic group. The predominant substitution is Ca + Mg ↔ Na + Al. The third, tin-stage tourmaline, is classified as schorl–dravite with some tourmalines being fluor-schorl, oxy-schorl, foitite and magnesio-foitite. The tin-stage tourmaline is characterised by the substitutions Fe 2+ ↔ Mg, Altot + O 2– ↔ Fe 2+ + OH –, and Fe 3+ ↔ Altot . An increase of the Fe 3+ /Fetot value from 3–9% in the molybdenum stage to 12–16% in the tin-stage tourmalines indicates an increase in oxidation potential, which possibly contributed to cassiterite deposition. Comparison of tourmalines from greisen, porphyry and intrusion-related tin deposits worldwide shows they differ in primary chemical substitutions so can be characterised by this mechanism. The Fe 3+ /Fetot value in tourmaline also appears to be one of the indications for the tin deposit type. The Fe3+ /Fetot value increases from <10% in greisen tourmaline through 15% in tourmaline from intrusion-related deposits to 20% in tourmaline from porphyry deposits.